Analisis Kemampuan Berpikir Tingkat Tinggi (HOTS) dalam Menyelesaikan Soal Materi Minyak Bumi dan Hidrokarbon - Hendra Ginanda; Effendi Effendi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The Independent Curriculum aims to form students who have the ability to think logically and critically. Therefore, this study was conducted to analyze students' high-level thinking skills (HOTS) in solving HOTS problems on Hydrocarbons and Petroleum materials. The subjects of this study are 30 students of class XI.1. The research uses a quantitative approach with descriptive data analysis. The research instrument is in the form of 8 HOTS questions in the form of descriptions. The results showed that 24% of students were in the high category, 70% in the medium category, 3% in the low category, and 3% in the very low category. Overall, the percentage of HOTS achievement is 71.35% and is included in the medium category. These findings indicate that the majority of students have not yet achieved a high level of HOTS, so a learning strategy that is more able to stimulate analytical and evaluative skills is needed.